(3JNQjL CMGOjK GdTQM GdcHjQ ddhLjRs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s; (3GdQGaYj , CHh GdbGSe YHO GdcQje Hf eMeO Hf YHO GdcQje GdQGaYj GdbRhjfj, GdQGaYj GdbRhjfj,J (B623 (3g` s ((3CMeO Hf YHO Gddg GdebQi s)
(3ChdgG (B:s
(3GdMeO ddg eNQL GdMi ef GdejJ heNQL GdejJ ef GdMi CeG HYO abO hbaJ Ydi JNQjL CMGOjK TQM GdhLjR cJGH GdWgGQI s
(3BNQgG (B:s
(3hjbGd (B: (3Ef YdjkG QLY Yf Pdc (B: (3bdJ (B: (3CNQLg YHO GdQGRb HESfGO UMjM , hGddg CYde BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdhLjR HMLI GdESdGe CHj MGeO eMeO Hf eMeO GdZRGdi J SfI (B505s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdMOjK h GdeUWdMs